Acute Management of Arrhythmias in Patients with Known Congenital Heart Disease - Bianchi, Francesca; Grossi, Stefano (The Arrhythmic Patient in the Emergency Department, 2016)
Focusing the issue. Arrhythmias and sudden death are frequent late complications of congenital heart disease (CHD) patients. Arrhythmia substrate and consequent management is peculiar for any CHD, but some general principles can be identified and recently international scientific boards have provided evidence-based recommendations on best practice. What physicians working in ED should know. Facing acute arrhythmias in CHD patients needs an early interplay between emergency physician and cardiologist. What cardiologist should know. Atrial tachyarrhythmias are the most frequent; severe and moderate complexity forms have a high predisposition to thromboembolic complications, most antiarrhythmic drugs are contraindicated or ineffective. Macro-reentrant ventricular tachycardia is a late complication in postoperative patients who have undergone ventriculotomy and/or patching. Indications for hospitalization, follow-up and referral. Syncope, ventricular arrhythmias and in general arrhythmias in the setting of moderate to severe complexity congenital heart disease should be hospitalized and a multidisciplinary staff involved